Scammarctus batei Holthuis 2002, n. comb. - Holthuis, Lipke B. (Zenodo, 2002)
Scammarctus batei (Holthuis, 1946) n. comb. (Figs 9-11; 66D, E) Scyllarus batei Holthuis, 1946: 94; 1984: Scylr.2, fig.; 1991: 219, figs 415, 416. — Estampador 1959: 40. — Robertson 1968: 334. — Prasad & Tampi 1969: 82. — Burukovsky 1974: 107; 1983: 151. — Prasad et al. 1980: 89, fig. 12. — Prasad 1983: 144, fig. 3c. — Chan & Yu 1986: 155, pl. 4, pl. 9 figs A, B; 1993: 205, col. fig. — Sekiguchi 1986a: 1290; 1987a: 331; 1987b: 415, 417. — Huang 1994: 564. Arctus orientalis Bate, 1888: 68, pl. 9 fig. 4. — Alcock & Anderson 1894: 165. — Alcock 1901: 181. — Lloyd 1907: 6. — Estampador 1937: 495 [non Scyllarus orientalis Lund, 1792 (= Thenus orientalis )]. Scyllarus orientalis – De Man 1916: 73. — Ramadan 1938: 126, fig. 2. — Sewell 1955: 200, 201, 203. Scyllarus batei batei – Holthuis 1960: 149. — George 1969: 433. — Phillips et al. 1980: 69. Scyllarus batei arabicus Holthuis, 1960: 149. — George 1969: 434. — Phillips et al. 1980: 69. — Fransen et al. 1998: 66. TYPE MATERIAL. — Syntypes: RV Challenger , stn 209, 2 specimens (BM), primarily identified as Arctus orientalis . TYPE LOCALITY. — Philippines, between Bohol and Cebu, at 10°14'N, 123°54'E, depth 174 m. MATERIAL EXAMINED. — Madagascar. RV Vauban , stn CH 44, 15°25.7'S, 46°01.0'E, 200-210 m, 7.XI.1972, 1 badly damaged c. 12 mm (MNHN-Pa 572). — Stn CH 93, 22°17.3'S, 43°05.9'E, 350 m, 27.XI.1973, 1 (MNHN-Pa 568). Mozambique. RV Prof. Mesyatsev , stn 66, 24°57.0'S, 35°07.1'E, 200-210 m, 25.I.1976, 2 (VNIRO). — RV Anton Bruun , cruise 8, stn 397A, 25°12'S, 34°04'E, shrimp trawl, 230-295 m, 29.IX.1964, 3 24- 30 mm, 1 25 mm (USNM). — RV Prof. Mesyatsev , stn 94, 25°31.8'S, 34°49.8'E, 220-225 m, 3.II.1976, 2, 2 (VNIRO). Kenya. RV Anton Bruun , cruise 8, stn 421G, 2°56'S, 40°28'E, shrimp trawl, 240 m, 8.XI.1964, 2 25 and 35 mm, 2 18 and 31 mm (USNM). — RV Fridtjof Nansen , stn 862, 3°26'S, 40°23'E, 484 m, 1 (RMNH D 33223). — RV Manihine cruise 377, stn 16, 3°08'S, 40°20.5'E- 3°7.5'S, 40°21'E, 250-255 m, muddy sand, Agassiz trawl, 5.IX.1974, A. J. Bruce leg., 7, 2 (1 ov.) (RMNH D 30865). — RV Prof. Mesyatsev , 3°04'S, 40°13.7'E, 200 m, 16.III.1976, 1 ov. (VNIRO). — RV Manihine , cruise 331, stn 4, 3°01'S, 40°22.5'E- 2°59.5'S, 40°24.6'E, 236-256 m, Agassiz trawl, 7.X.1971, A. J. Bruce and P. S. Sandhu leg., 1 (RMNH D 45643). Gulf of Aden. John Murray Expedition, stn 194, 13°16'- 13°16'36"N, 46°20'24"- 46°14'E, 220 m, 7.V.1934, 3, 2 ov. (USNM). South coast of Arabia. RV Investigator , 17°59'N, 57°22'30"E, 285-366 m, 1 (USNM). West coast of India (off Calicut) (= Kozhikode). RV Investigator , 183 m, 1 ov. (AM P.2639). South China Sea. South of Hainan, RV Cape St. Mary , cruise 4/64, stn 34, trawl 189, 17°10.0'N, 109°51.0'E- 17°12.5'N, 109°53.5'E, 205-212 m, fine mud, Granton trawl, 5.VIII.1964, A. J. Bruce leg., 1 (RMNH D 24947). Taiwan. Tong-Kang, Ping-Tong County, 31.X.1984, T. Y. Chan leg., 1 (RMNH D 39340). Philippines. Malavatuan Id, RV Albatross , S 23°E, 8.5 miles, stn D 5278, 14°00'10"N, 120°17'15"E, 146- 187 m, fine sand or fine sand with mud and shells, 17.VII.1908, 1 (USNM). Corregidor Light, N 26°E, 25.5 miles, stn D 5272, 14°N, 120°22'30"E, 216 m, mud, shells and coral sand, 14.VII.1908, 1. Tayabas Light (outer), N 43°W, 6 miles, stn D 5371, 13°49'40"N, 121°40'15"E, 152 m, green mud, 24.II.1909, 2, 1 ov.. — N 50°W, 8.8 miles, stn D 5369, 13°48'N, 121°43'E, 194 m, black sand, 24.II.1909, 1, 1. — N 9°E, 7.4 miles, stn D 5374, 13°46'45"N, 121°35'08"E, 348 m, grey mud, 2.III.1909, 1. Sombrero Id, S 47°E, 10 miles, stn D 5118, 13°48'45"N, 120°41'51"E, 216-291 m, dark green mud, 21.I.1908, 1. Matocot Point, Luzon, N 80°E, 33.30 miles, stn D 5265, 13°41'15"N, 120°00'50"E, 247 m, sand and mud, 6.VI.1908, 2, 2. Legaspi Light, S 58°W, 4.5 miles, stn D 5453, 13°12'N, 123°49'18"E, 267 m, 7.VI.1909, 2. Off SE Mindoro, Balanja Point, N 80°W, 6 miles, stn D 5261, 12°30'55"N, 121°34'24"E, 265 m, sand and mud, 6.VI.1908, 1. Between Leyte and Cebu, Capitancillo Id Light, S 46°W, 15.7 miles, stn D 5403, 11°10'N, 124°17'15"E, 333 m, green mud, 16.III.1909, 1. — N 25°W, 20.8 miles, stn D 5408, 10°40'15"N, 124°15'E, 291 m, green mud, 18.III.1909, 4 (1 nisto). Mindanao, Point Tagolo Light, S 80°W, 9.7 miles, stn D 5516, 8°46'N, 123°32'30"E, 320 m, globigerina, 9.VIII.1909, 1, 1 (USNM). MUSORSTOM 1. Near Pulau Lubang, W of Luzon, stn 2, 14°02.0'N, 120°17.8'E, 182-187 m, 19.III.1976, 1 (MNHN-Pa 709). — Stn 3, 14°01.5'N, 120°15.3'E, 183-185 m, 19.III.1976, 1 (MNHN). — Stn 9, 13°59.5'N, 120°17.6'E, 180- 194 m, 19.III.1976, 2 (MNHN-Pa 710). — Stn 11, 14°00.9'N, 120°21.5'E, 217-230 m, 20.III.1976, 3, 2 (MNHN-Pa 719). — Stn 12, 14°00.45'N, 120°17.2'E, 187-210 m, 20.III.1976, 7, 3 (2 ov.) (MNHN-Pa 693). — Stn 21, 14°02.8'N, 120°24.3'E, 174-223 m, 21.III.1976, 1 (MNHN-Pa 700). — Stn 24, 14°01.7'N, 120°20.2'E, 189-209 m, 22.III.1976, 3 (MNHN-Pa 704). — Stn 25, 14°02.0'N, 120°18.0'E, 191-200 m, 22.III.1976, 3, 2 (MNHN-Pa 703). — Stn 30, 13°59.7'N, 120°16.7'E, 177-186 m, 22.III.1976, 1 (MNHN-Pa 713). — Stn 32, 13°59.4'N, 120°18.0'E, 184-193 m, 23.III.1976, 1 (MNHN- Pa 724). — Stn 34, 13°59.2'N, 120°15.8'E, 188- 191 m, 23.III.1976, 2 (MNHN-Pa 701). — Stn 36, 14°00.3'N, 120°17.0'E, 187-210 m, 23.III.1976, 5, 3 (MNHN-Pa 702 and 712). — Stn 40, 13°58.3'N, 120°29.4'E, 265-287 m, 24.III.1976, 1 (MNHN-Pa 711). — Stn 42, 13°54.1'N, 120°29.1'E, 379-407 m, 24.III.1976, 1, 1 (MNHN-Pa 705). — Stn 61, 13°59.7'N, 120°16.8'E, 184-202 m, 27.III.1976, 1 (MNHN-Pa 708). — Stn 65, 14°00.8'N, 120°16.2'E, 194-202 m, 27.III.1976, 1 (MNHN-Pa 698). — Stn 68, 13°58.8'N, 120°19.0'E, 183-199 m, 27.III.1976, 8, 4 (3 ov.) (MNHN-Pa 691-692). — Stn 69, 14°00.9'N, 120°19.0'E, 187-199 m, 27.III.1976, 1 (MNHN- Pa 699). MUSORSTOM 2. Between Luzon, Pulau Lubang and Mindoro, stn 11, 14°00.1'N, 120°18.9'E, 194- 196 m, 21.XI.1980, 4, 2 (1 ov.) (MNHN- Pa 689). — Stn 12, 14°02.0'N, 120°21.0'E, 197- 210 m, 21.XI.1980, 1 (MNHN-Pa 715). — Stn 13, 13°59.7'N, 120°19.2'E, 193-200 m, 21.XI.1980, 2, 2 (1 ov.) (MNHN-Pa 688). — Stn 18, 14°00.2'N, 120°17.2'E, 188-195 m, 22.XI.1980, 1 (MNHN-Pa 717). — Stn 20, 13°59.5'N, 120°18.2'E, 185-192 m, 22.XI.1980, 2, 1 (MNHN-Pa 687). — Stn 21, 14°02.2'N, 120°17.4'E, 191-192 m, 22.XI.1980, 4 (MNHN-Pa 684). — Stn 51, 14°00.4'N, 120°17.6'E, 170-187 m, 27.XI.1980, 1 (MNHN-Pa 721). — Stn 52, 13°59.1'N, 120°18.8'E, 181-190 m, 27.XI.1980, 2 (1 ov.) (MNHN-Pa 722). — Stn 64, 14°00.1'N, 120°18.2'E, 191-195 m, 29.XI.1980, 1 (MNHN-Pa 716). — Stn 66, 14°00.1'N, 120°18.7'E, 192-209 m, 29.XI.1980, 1, 3 (MNHN-Pa 686). — Stn 67, 14°01.8'N, 120°19.3'E, 193-199 m, 29.XI.1980, 1, 1 ov. (MNHN-Pa 1919). — Stn 68, 14°00.5'N, 120°17.5'E, 195-199 m, 29.XI.1980, 1, 3 (1 ov.) (MNHN-Pa 685). — Stn 71, 14°01.2'N, 120°19.1'E, 189-197 m, 30.XI.1980, 2, 2 ov. (MNHN-Pa 690). MUSORSTOM 3. Between Luzon, Pulau Lubang and Mindoro, stn CP 87, 14°00'N, 120°19'E, 191- 197 m, 31.V.1985, 2 25 and 26 mm (MNHN- Pa 1089). — Stn CP 97, 14°00'N, 120°18'E, 189-194 m, 1.VI.1985, 1 14 mm (MNHN-Pa 1086). — Stn CP 98, 14°00'N, 120°18'E, 194-205 m, 1.VI.1985, 1 juv. 13 mm (MNHN-Pa 1078). — Stn CP 99, 14°01'N, 120°19'E, 196-204 m, 1.VI.1985, 1 ov. 26 mm (MNHN-Pa 1077). — Stn CP 100, 14°00'N, 120°18'E, 189-199 m, 1.VI.1985, 2 20 and 25 mm (MNHN-Pa 1088). — Stn CP 101, 14°00'N, 120°19'E, 194-196 m, 1.VI.1985, 3 14-26 mm (MNHN-Pa 1083). — Stn CP 103, 14°00'N, 120°18'E, 193-200 m, 1.VI.1985, 2 13 and 25 mm (USNM 1000671 and MNHN-Pa 1081). — Stn CP 108, 14°01'N, 120°18'E, 188-195 m, 2.VI.1985, 2 14 and 26 mm (MNHN-Pa 1080). Between Mindoro and Panay, stn CP 120, 12°06'N, 121°15'E, 219-220 m, 3.VI.1985, 5 15-22 mm, 3 15-24 mm (RMNH D 48731). — Stn CP 138, 11°54'N, 122°15'E, 252-370 m, 6.VI.1985, 1 17 mm (MNHN-Pa 1085). — Stn CP 139, 11°53'N, 122°14'E, 240-267 m, 6.VI.1985, 3 12-25 mm, 7 16-23 mm (MNHN-Pa 1073). Off Cebu, stn CP 145, 11°01'N, 124°04'E, 214- 246 m, 7.VI.1985, 1 juv. 11 mm, 1 juv. 14 mm (MNHN-Pa 1082). Between Cebu and Leyte, stn CP 143, 11°29'N, 124°11'E, 205-214 m, 7.VI.1985, 1 24 mm (MNHN-Pa 1075). West of Borneo. RV Cape St. Mary , cruise 7/64, stn 43, trawl 251, 5°28.9'N, 110°08.9'E- 5°26.8'N, 110°11.0'E, 172-179 m, clayey mud, 7.XI.1964, A. J. Bruce leg., 1 (RMNH D 24948). Indonesia. Makassar Strait, CORINDON, stn 267, 1°56.6'S, 119°16.7'E, 134-186 m, 7.XI.1980, 7, 1 (MNHN-Pa 723). — Stn 271, 1°57.8'S, 119°15.0'E, 215-252 m, 7.XI.1980, 22 specimens. — Stn 273, 1°56.0'S, 119°16.0'E, 180-220 m, 7.XI.1980, 33, 3 (MNHN-Pa 718). Australia. Arafura Sea, FV Noble Pearl , 09°46'S, 130°00'E, 244-300 m, XI-XII.1987, T. Bradley leg., A. J. Bruce don., 1 (RMNH D). New Caledonia. BIOCAL, stn CP 105, 21°31'S, 166°22'E, 330-335 m, 8.IX.1985, 1 18 mm (MNHN-Pa 1160). BATHUS 1, stn CP 670, 20°54.05'S, 165°53.38'E, 394-397 m, 14.III.1993, 1 18 mm (MNHN-Pa 1866). — Stn CP 702, 30°55.97'S, 165°34.67'E, 531- 660 m, 18.III.1993, 3 16-18 mm (MNHN-Pa 1863). — Stn CP 709, 31°42.72'S, 166°35.75'E, 347- 375 m, 9.III.1993, 2 19 and 20 mm, 1 19 mm (MNHN-Pa 1864). — Stn CP 710, 31°43.16'S, 166°36.35'E, 330-386 m, 19.III.1993, 1 17 mm, 2 18 mm (RMNH D 48732). BATHUS 2, stn CP 742, 32°33.45'S, 166°25.86'E, 340-470 m, 14.V.1993, 1 16 mm (MNHN-Pa 1875). HALIPRO 1, stn CP 851, 21°43'S, 166°37'E, 314- 364 m, 19.III.1994, 2 18 and 19 mm, 1 17 mm (RMNH D 48730). — Stn 856, 21°44'S, 166°37'E, 311-365 m, 20.III.1994, 1 18 mm, 1 17 mm (MNHN-Pa 1916). BATHUS 4, stn CP 899, 20°16.68'S, 163°50.26'E, 500-600 m, 3.VIII.1994, 1 19 mm (USNM 1000673). — Stn CP 946, 20°33.81'S, 164°58.35'E, 386-430 m, 10.VIII.1994, 3 19-20 mm (MNHN-Pa 1903). — Stn CP 952, 20°34.70'S, 164°58.76'E, 316- 270 m, 10.VIII.1994, 3 16- 19 mm (MNHN-Pa 1902). Vanuatu (New Hebrides). MUSORSTOM 8, stn CP 1121, 15°06.97'S, 166°53.42'E, 315-360 m, 9.X.1994, B. Richer de Forges leg., 2 17 and 19 mm, 2 ov. 19 and 20 mm (MNHN-Pa 1891). — Stn CP 1123, 15°07.19'S, 166°55.20'E, 262- 352 m, 9.X.1994, B. Richer de Forges leg., 3 16- 18 mm (MNHN-Pa 1868). — Stn CP 1135, 15°40.50'S, 167°02.43'E, 282-375 m, 11.X.1994, B. Richer de Forges leg., 2 15 and 20 mm, largest ov. (RMNH D 48733). Fiji Islands. MUSORSTOM 10, Bligh Water, N of Viti Levu, stn CP 1318, 17°15.6'S, 178°03.4'E, 330- 335 m, 6.VIII.1998, 1 16 mm (photographed) (MNHN-Pa 1886). — Stn CP 1320, 17°16.8'S, 177°53.6'E, 290-300 m, 6.VIII.1998, 1 16 mm (MNHN-Pa 1844). — Stn CP 1325, 17°16.4'S, 177°49.8'E, 282-322 m, 7.VIII.1998, 1 17 mm, 3 17-19 mm (MNHN-Pa 1867). — Stn CP 1326, 17°14.3'S, 177°49.7'E, 265-300 m, 7.VIII.1998, 2 15 and 17 mm, 1 17 mm (RMNH D 48735). SE of Viti Levu, stn CP 1348, 17°30.3'S, 178°39.6'E, 353-390 m, 11.VIII.1998, 24 16-18 mm, 26 15-19 mm (MNHN-Pa 1865; RMNH D 48734; USNM 1000674). — Stn CP 1349, 17°31.1'S, 178°38.8'E, 244-252 m, 11.VIII.1998, 3 16- 17 mm (MNHN-Pa 1872). — Stn 1351, 17°31.1'S, 178°40.0'E, 292-311 m, 11.VIII.1998, 2 15 and 16 mm, 2 16 and 18 mm (MNHN-Pa 1870). — Stn CP 1355, 17°49.5'S, 178°49.4'E, 302-310 m, 12.VIII.1998, 2 15 and 18 mm (USNM 1000672). S of Viti Levu, stn CP 1390, 18°18.6'S, 178°05.1'E, 234-361 m, 19.VIII.1998, 1 17 mm (MNHN-Pa 1904). BORDAU 1. N of Vanua Levu, stn CP 1402, 16°38'S, 179°36'E, 260-279 m, 25.II.1999, 1 16 mm (photographed, MNHN-Pa 1846), 2 15 and 16 mm (MNHN-Pa 1847). DISTRIBUTION. — This characteristic species has a wide distribution in the Indo-West Pacific region extending from the east coast of Africa (Gulf of Aden to Mozambique and Madagascar) to Taiwan, the South China Sea, the Philippines and Indonesia, N Australia, New Caledonia and Vanuatu. The western form has been separated from the typical form as a subspecies arabicus by Holthuis (1960). The type locality of the species is RV Challenger , stn 209, between Bohol and Cebu, Philippines, at 10°14'N, 123°54'E, depth 174 m, bottom blue mud. The two syntypes of Arctus orientalis Bate, 1888, for which Scyllarus batei Holthuis, 1946 is a new name, are preserved in the Natural History Museum, London. HABITAT. — The species is known from depths of 152-531(531-660) m; most records are from 152 to 400 m, with a peak between 152 and 200 m. A soft bottom is evidently preferred, it has been described as: fine mud; green mud (four times); dark green mud; grey mud; globigerina ooze; clayey mud; mud, shells and coral sand; sand and mud (twice); fine sand or fine sand with mud and shells; black sand. DESCRIPTION The carapace is rather flat and not strongly uneven; it is covered by a short pubescence. The rostrum is truncate, and somewhat constricted behind the top. It bears a small, low, and blunt tubercle, but no tooth. The postrostral carina shows a pregastric, a gastric and a cardiac tooth, all of which are rather low. The pregastric tooth lies somewhat closer to the gastric tooth than to the rostrum, it is rather broad and almost as strong as the gastric tooth, sometimes it has a double top. There are a few small tubercles behind and in front of it. The gastric tooth is somewhat stronger than the pregastric, it ends in a single or double top and is followed by a double row of eight to 12 indistinct squamiform tubercles. The cardiac tooth has the apex blunt or bilobed and is followed by a double row of nine to 16 low squamiform tubercles. Immediately before the cardiac tooth, below its top, there is a pair of small, but distinct tubercles, placed side by side in the cervical groove. The anterior and posterior submedian carinae each bear a group of tubercles, which are most conspicuous anteriorly, where the carina sometimes is somewhat elevated. The branchial carina of the carapace is widely interrupted by the cervical groove. In the gap, just before the anterior end of the posterior carina, there is a sometimes small but always distinct tubercle. The anterior branchial carina ends in two low and blunt teeth, which are placed, one behind the other, on the inner margin of the orbit. The rest of the anterior branchial carina is entire. The posterior branchial carina ends anteriorly in a distinct tooth and bears behind that a single row of about 20 indistinct to very indistinct squamiform tubercles. The intermediate row consists of about six or seven blunt tubercles; furthermore there are a few tubercles at either side of the posterior branchial carina. The lateral margin of the carapace shows a narrow cervical incision and a wider postcervical. Apart from those mentioned, the region between the post- rostral and branchial carinae shows no tubercles. There are about five to seven anterolateral teeth, four or five mediolateral and 12 to 16 posterolateral teeth; all these teeth, apart from the first of each group, show as vague serrations. Between the posterior branchial and posterolateral carinae there are a few small tubercles which are placed close to these carinae leaving the intermediate region smooth. In this same region there is a short blunt oblique carina right behind the cervical groove; it shows some blunt squamiform markings. There are one or two postorbital tubercles, which are small and partly hidden by the pubescence. The marginal groove is wide and rather shallow. Before it there are two, behind it one to three transverse rows of rather indistinct tubercles. The posterior margin of the carapace is emarginate in the middle. In the first abdominal somite the transverse groove is widely interrupted in the middle. The median area of the somite is smooth, like the surface before and behind the groove; however, the posterior half may show indistinct traces of longitudinal grooves. In the next four somites the anterior half of the dorsal surface is entirely smooth. The posterior half is higher and bears a distinct, slightly elevated median carina; in the anterior of the four somites these carinae are slightly higher than in the posterior. The carinae of somites II to IV usually show an indistinct longitudinal groove. The carinae are lobulated at their base. The upper surface of each somite bears a wide transverse groove, which is interrupted by the median carina; this groove extends on to the pleuron. In its distal part, above the base of the pleuron the groove shows two anterior side grooves, which extend into the anterior part of the somite. There is, however, no distinct arborescent pattern of grooves as found in Scyllarus arctus and related species. In the pleuron of the second somite the transverse groove curves forward and slightly up. In the following pleura the groove is straight and ends in the distal part of the pleuron, however, a second groove is placed in the anterior half of the pleura of somites III to V. The upper surface of the somites shows indistinct squamiform tubercles, which may give the anterior margin of the transverse groove a lobulated appearance. The posterior margin of the first to third abdominal somites is slightly emarginate in the middle, sometimes, however, this emargination is hardly noticeable. The pleura are rather broad. That of the first somite is bilobed, the anterior lobe being widest. The pleura of somites II to V have the tip bluntly pointed and directed backward, while the margins are indistinctly serrate or practically smooth. The sixth abdominal somite shows some wide grooves and very few but large tubercles. On the end of the hard part of the telson there are two pairs of teeth, the teeth of the outer pair are placed on the margin of the telson and are broad and bluntly angular. The inner pair is narrower and more acute, it is placed in the median part of the telson at a more anterior level than the outer pair. The anterior margin of the antennular somite bears a low and blunt but distinct tooth in the middle of each half. The anterior margin of the distal (sixth) segment of the antenna is convex and bears five or six teeth, while a very small tooth is found on the inner margin. The teeth are rather elongate triangular, tapering regularly toward the narrowly rounded top; hereby the incisions between the teeth are wide. The fifth segment of the antenna shows a distinct blunt tooth on the inner margin; this tooth bears a dorsal carina. The anterior margin of the fourth segment bears three to seven teeth (not including the apical tooth), the inner of which is the largest. The outer margin of this segment bears two or three large teeth (again the apical one not included); behind these large teeth sometimes an extremely small additional tooth may be seen, while at the base of the apical tooth there sometimes are one or two small denticles. The apical tooth is strong and often reaches beyond the outer part of the distal margin of the sixth segment. The upper surface of the fourth segment shows a single strong oblique carina, which ends in the apical tooth; there are no additional carinae or tubercles on the outer half of the segment. The anterior margin of the epistome is slightly sinuous or somewhat V-shaped, with an incision in the middle. The third maxilliped in situ is only partly visible, being mostly hidden behind the first pereiopods. The pereiopods of this species, especially the fourth and fifth, are unusually long and slender, much more so than in most other Scyllarid species. P.1 is only slightly more heavy than P.2. In P.1 and P.2 the dactylus is naked, or has a few short hairs in the extreme : Published as part of Holthuis, Lipke B., 2002, The Indo-Pacific scyllarine lobsters (Crustacea, Decapoda, Scyllaridae), pp. 499-683 in Zoosystema 24 (3) on pages 520-526, DOI: 10.5281/zenodo.4689240 : {"references": ["HOLTHUIS L. B. 1946. - The Stenopodidae, Nephropsidae, Scyllaridae and Palinuridae. The Decapoda Macrura of the Snellius Expedition. I. Biological results of the Snellius Expedition. XIV. Temminckia 7: 1 - 178, text-figs 1, 2, pls 1 - 11.", "HOLTHUIS L. B. 1984. - Lobsters. Western Indian Ocean (Fishery Area 51). FAO Species Identification Sheets for Fishery Purposes 5, 62 p., figs.", "ESTAMPADOR E. 1959. - Revised check list of Philippine Crustacean Decapods. Natural and Applied Science Bulletin, Manila 17: 1 - 127.", "ROBERTSON P. B. 1968. - The complete larval development of the Sand Lobster, Scyllarus americanus (Smith), (Decapoda, Scyllaridae) in the laboratory, with notes on larvae from the plankton. Bulletin of Marine Science, University of Miami 18: 294 - 342, figs 1 - 20.", "PRASAD R. R. & TAMPI P. R. S. 1969. - On the distribution of Palinurid and Scyllarid lobsters in the Indian Ocean. Journal of the Marine Biological Association of India 10: 78 - 87, figs 1, 2.", "BURUKOVSKY R. N. 1974. - Keys for the Identification of Shrimps, Spiny Lobsters and Lobsters. Pishchevaya Promyshlennost Publishers, Moscow, 126 p., 189 figs (in Russian).", "BURUKOVSKY R. N. 1983. - Key to shrimps and lobsters. Russian Translation Series 5, A. A. Balkema, Rotterdam: i-xi, 1 - 174, figs 1 - 189 (English translation of Burukovsky 1974).", "PRASAD R. R., TAMPI P. R. S. & GEORGE M. J. 1980. - Phyllosoma larvae from the Indian Ocean collected by the Dana Expedition 1928 - 1930. Journal of the Marine Biological Association of India 17 (2): 56 - 107, figs 1 - 17.", "PRASAD R. R. 1983. - Distribution and growth. Studies on the phyllosoma larvae from the Indian Ocean: I. Journal of the Marine Biological Association of India 20: 143 - 156, figs 1 - 13.", "CHAN T. - Y. & YU H. - P. 1986. - A report on the Scyllarus lobsters (Crustacea: Decapoda: Scyllaridae) from Taiwan. Journal of the Taiwan Museum 39 (2): 147 - 174, text-figs 1, 2, pls 1 - 10.", "SEKIGUCHI H. 1986 a. - Identification of late-stage phyllosoma larvae of the scyllarid and palinurid lobsters in the Japanese waters. Bulletin of the Japanese Society of Scientific Fisheries 52 (8): 1289 - 1294.", "SEKIGUCHI H. 1987 a. - Life histories of the scyllarid and palinurid lobsters - 11. Aquabiology, Tokyo 9 (5): 330 - 335, figs 46, 47.", "SEKIGUCHI H. 1987 b. - Life histories of the scyllarid and palinurid lobsters - 12. Aquabiology, Tokyo 9 (6): 415 - 419, figs 48 - 50.", "HUANG Z. - G. 1994. - Marine Species and their Distributions in China's Seas. China Ocean Press, Beijing, 11 + 141 p.", "BATE C. S. 1888. - Report on the Crustacea Macrura collected by H. M. S. Challenger during the years 1873 - 76. Report on the Scientific Results of the Voyage of H. M. S. Challenger, during the Years 1873 - 76 (Zool.). Her Majesty's Stationery Office, London, 24, xc + 942 p., 76 text-figs, 150 pls.", "ALCOCK A. & ANDERSON A. R. S. 1894. - An account of a recent collection of deep sea Crustacea from the Bay of Bengal and Laccadive Sea. Natural history notes from H. M. Indian Marine Survey Steamer \" Investigator \", commander C. F. Oldham, R. N., commanding. Series II, No. 14. Journal of the Asiatic Society of Bengal 63 (2): 141 - 185, pl. 9.", "ALCOCK A. 1901. - A Descriptive Catalogue of the Indian Deep-Sea Crustacea Decapoda Macrura and Anomala in the Indian Museum. Being a Revised Account of the Deep-Sea Species Collected by the Royal Indian Marine Survey Ship Investigator. Trustees of the Indian Museum, Calcutta: 286 + iv p., 3 pls.", "LLOYD R. E. 1907. - Contributions to the fauna of the Arabian Sea, with descriptions of new fishes and Crustacea. Records of the Indian Museum 1: 1 - 12.", "ESTAMPADOR E. P. 1937. - A check list of Philippine Crustacean Decapods. Philippine Journal of Science 62: 465 - 559.", "DE MAN J. G. 1916. - Families Eryonidae, Palinuridae, Scyllaridae and Nephropsidae. The Decapoda of the Siboga Expedition. Part III. Siboga Expeditie Monographie 39 (a 2): 1 - 122, pls 1 - 4.", "RAMADAN W. W. 1938. - The Astacura and Palinura. Scientific Reports the John Murray Expedition 1933 - 34 5 (5): 123 - 145, 12 figs.", "SEWELL R. B. S. 1955. - A study of the sea coast of southern Arabia. Proceedings of the Linnean Society of London 1952 - 1953: 188 - 210, figs 1 - 10.", "HOLTHUIS L. B. 1960. - Preliminary descriptions of one new genus, twelve new species and three new subspecies of Scyllarid lobsters (Crustacea Decapoda Macrura). Proceedings of the Biological Society of Washington 73: 147 - 154.", "GEORGE M. J. 1969. - Two new records of scyllarid lobsters from the Arabian Sea. Journal of the Marine Biological Association of India 9: 433 - 435.", "FRANSEN C. H. J. M., HOLTHUIS L. B. & ADEMA J. P. H. M. 1998. - Type-catalogue of the Decapod Crustacea in the collections of the Nationaal Natuurhistorisch Museum, with appendices of pre- 1900 collectors and material. Zoologische Verhandelingen, Leiden 311: 1 - 344, figs 1 - 79.", "CHAN T. - Y. & YU H. - P. 1993. - The Illustrated Lobsters of Taiwan. SMC Publishing Inc., Taipei, x + 247 p., figs."]}